Real‐time data collection to improve energy efficiency: A case study of food manufacturer. Issue 8 (11th December 2019) - Jagtap, Sandeep; Rahimifard, Shahin; Duong, Linh N. K.
Abstract: The rising price and demand for energy are significant issues for the food sector, which consumes a substantial amount of energy throughout the supply chain. Hence, improving energy efficiency has become an essential priority for the food sector. However, most food businesses have limited awareness of the recent technological advancements in real‐time energy monitoring. Thus, the concept of "Internet of Things" (IoT) has been investigated to increase the visibility, transparency, and awareness of various energy usage levels. This paper presents a case study of a beverage factory where the implementation of an IoT‐enabled sensing technology based on the embodied product energy (EPE) model helped to reduce the energy consumption. This arrangement made provision for the collection of real‐time energy data within a food production system to support informed and energy‐aware operational decisions, which lead to optimized energy consumption and significant savings of approximately 163, 000 kWh in the year 2017. Practical applications: Given the importance of energy efficiency and Internet of Things (IoT), especially in the food manufacturing industry, this research reports a baseline application at a beverage company in India. The results allowed the company to use energy more efficiently to have an advantage over its competitors and better market positioning. More data could be incorporated into the energy management system with the use of IoT. The availability and accuracy of such valuable data would help managers to make better energy‐efficient decisions.